Z rozważań o chuligańskim charakterze zachowań przestępnych w ujęciu polskiego prawa karnego - Kokot, Rajnhardt (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article presents the problem of a hooligan type of behaviour and its criminal law assessment.It presents the general image of the origin and the evolution of hooligan behaviour in the Polish legal system. It also makes an attempt at explaining the features of this subject, which are included in its definition Art. 115 § 21 Criminal Code. The article also refers generally to the common doubts and dilemmas on the grounds of doctrine and judicial decision, which are caused by the ambiguities of sources and assessments. This in practice leads to the serious risk associated with making a uniform decision in the hooligan-type offences. The author also mentions the hooligan behaviour in the foreign legal systems, pointing out different functions which this behaviour can have. As an added bonus, the analysis also pays attention to some consequences of the hooligan-type offences within the criminal system, mentioning the changes that took place with the amendment of the Criminal Code of 1997, as of the 1st of July 2015.
Keywords: przestępstwa o charakterze chuligańskim; polskie prawo karne; nowelizacja kk 2015; orzecznictwo